Natural based biocomposite material for prosthetic socket fabrication - Che Me, Rosalam; Ibrahim, Rahinah; Md. Tahir, Paridah (Faculty of Design & Architecture, Universiti Putra Malaysia, 2012)
Artificial limbs may be needed for a variety of reasons including diseases, accidents, and congenital defects. As the human body changes over time due to growth or change in body weight, the artificial limbs have to be changed and adjusted periodically. This constant need for change or adjustment may become costly if the material used is expensive. This study will emphasise the prosthetic legs by focusing on the socket part as it is often changed and replaced with natural-based bio composites. We posit that natural fibre-based bio composites, such as the natural based reinforced plastic, have the same qualities of existing materials that can be used in various applications,. The results of this study are based on the compatibility of the properties of existing and proposed materials which contribute towards providing alternative materials that are more cost efficient, eco-friendly and yet maintaining the features required for artificial limbs. The findings are expected to help patients or wearers to live independently when they are young, who cannot afford to have this essential